Napsin a expression across subtypes of thyroid carcinoma: an immunohistochemical diagnostic encounter with prognostic correlates - Sheta, Heba; Maha M. Fawzy; Abd El hafez, Amal; Amr Hossam; Sherihan I. Gouda; Ahmad Darwish; Alemam, Doaa Sh.; Reham Alghandour; Doaa H. Sakr (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Novel aspartic proteinase of pepsin family A (Napsin A) is a diagnostic marker for pulmonary adenocarcinoma. Recently, it was detected in carcinomas of various organs including thyroid carcinomas (TCs), raising a diagnostic challenge especially when combined with positive thyroid transcription factor-1 (TTF-1). Methods: This retrospective study investigates the frequency of Napsin A immunohistochemical (IHC) expression across subtypes of TC focusing on its association with the prognostic parameters. Sixty-three TC patients who underwent thyroidectomy were enrolled. After collecting the clinicopathological, laboratory, surgical, therapeutic and survival data, IHC was applied to TC tissue microarray-prepared sections using anti-Napsin A. IHC scoring divided TCs as: Napsin A positive & negative. Statistical and survival analyses were performed using SPSS version 26. Results: Napsin A was expressed in 17.5% of TCs with 100% expression in anaplastic TC and 19.5% expression in papillary TC. Other TC subtypes were negative. Statistically significant associations were noticed between Napsin A and some less favorable TC prognostic variables as the involvement of both lobes, anaplastic histopathology, larger tumor size, higher pathological stage, and a shorter mean OS and DFS of patients (all P ≤0.05). Conclusions: Napsin A is predominately expressed in anaplastic and papillary TC subtypes. In patients with a possible metastatic lung carcinoma or malignancy of unknown origin co-expressing Napsin A and TTF-1, the diagnosis of TC should be considered and supported with a panel of other TC markers. Considering its less favorable prognostic associations, Napsin A may be added as a molecular marker for TC risk stratification, and treatment targeting. However, the other subtypes must be evaluated in a larger series to support these conclusions.